ORIENTEERING SITUATION TESTS IN THE FUNCTION OF PREDICTING SUCCESS OF POLICE OFFICERS IN TOPOGRAPHY FIELD TRAINING - Boban Milojković; Milivoj Dopsaj (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
The sample of 45 students (15 students of the I year of Police Academy - the members of orienteering section - Group 1, 15 students of the I year of Police Academy - Group 2 and 15 students of Advanced School of Interior Affairs - Group 3) has been chosen to test the degree of success in topography field training through several stages, and orienteering situation tests were used in one of these stages. The research was carried out following the completed theoretical and practical training in topography by the same teacher but according to various models. During the research, three batteries of tests were used, the tests of capability of fast and accurate reading of topographic maps in the form of perforated sections (T-1, T-2 and T-3). With regard to measuring success in solving orienteering situation tests of three tested groups based on which the educational efficiency of police members in topography field training should have been evaluated, the obtained results have shown that at a general level there were statistically important differences of total variance of the observed set of variables of tested groups at the level p = 0.000 (Willks Lambda, 0.056, F = 225.598). The results have shown that there were statistically important differences between the success in test solving with reference to groups at the level p = 0.002 and p = 0.000, respectively. Thedifferences between groups in the function of an individual test were as follows: T-1, there was a cross difference between all three groups; T-2, there was no difference between the first and second groups, but the third group differed in relation to the first and second ones; T-3, there was a cross difference between all three groups. The results of tested population by means of the stated instruments describe the level of competency of police members in topography respectively in order to individualize training, but primarily prove statistically considerable difference of the level of training between groups that participated in the research, as well as appropriateness of using techniques of orienteering as a sport of particular importance for police and armed forces.